FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PENGUNGKAPAN TANGGUNGJAWAB SOSIAL DAN LINGKUNGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Herlina, Herlina (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2016)
Factors That Influence The Policy Of Social Disclosure And Environmental Responsibility In Companies Listed On The Indonesia Stock Exchange. The aim of this study is to examine and provide empirical evidence about the factors that influence the policy of social disclosure and environmental responsibility in companies listed on the indonesia stock exchange, the observation period from 2007 until 2013. The sample obtained by 46 companies with 322 observations. The result  of  hypothesis  test  showed  that  the  size  of  the  company's significant   impacts  on  the  policy  of  social  disclosure  and  environmental responsibility.  The result  of  hypothesis  test  showed  that  the  leverage  had  no significant  impacts  on  the  policy  of   social  disclosure  and  environmental responsibility. The result of hypothesis test showed that  the profitability had no significant  impacts  on            the  policy  of  social  disclosure  and   environmental responsibility.   The   result   of   hypothesis   test   showed   that   the   board   of commissioners had no significant impact on the  policy of social disclosure and environmental responsibility. The result of hypothesis test showed that the size of the  company's  significant   impacts  on  the  policy  of  social  disclosure  and environmental responsibility. The result of hypothesis test showed that managerial ownership had no significantly impacts on the policy of  social disclosure and environmental responsibility. And The result of hypothesis test results  showed that the age of firm had no  significant impacts on the policy of social  disclousure and environmental responsibility.Keyword :   leverage, profitability, board of commissioners, size of company, managerial ownership, age of firm, CSR